(untitled) (Englisia : Journal of Language, Education, and Humanities, 2025)
The international teaching practicum provides pre-service English teachers with opportunities to enhance their professional experiences and develop their teacher identity. This study explores the professional identity development of two Indonesian pre-service English teachers during a one-month teaching practicum in the Philippines, focusing on the factors shaping this process through the lens of teacher professional identity. The research centers on two students from the English Education Department at a private university in Yogyakarta. Employing a qualitative narrative approach, data were gathered through semi-structured interviews and analyzed thematically within the framework of teacher professional identity. Findings reveal that the practicum significantly advanced the participants’ professional identity across its key dimensions. Mentor teachers’ guidance, positive student relationships, and a supportive practicum environment were critical to this development. These results highlight the interplay between individuals and their environment, emphasizing the need for a nurturing setting to foster personal and professional growth.